PENGARUH WAKTU CURING TERHADAP KUAT TEKAN GEOPOLIMER BERBASIS FLY ASH - Andrie Harmaji; Claudia Claudia; Lia Asri; Bambang Sunendar; Ahmad Nuruddin (UNIVERSITAS KEBANGSAAN, 2019)
Abstract:. Suralaya power plant produces fly ash about 219.000 ton per year. Fly ash contents of silica and alumina as major components that can be used as precursors for geopolymer, a three dimensional networks aluminosilicate polymers. This research aim is to utilize fly ash for geopolymer made by mixing fly ash, fine aggregate, and alkali activator in a cubic mould and curing was carried out at room temperature for 7 and 28 days. After 28 days of curing the compressive strength of geopolymer reached 41.70 MPa. XRD characterization shows Albite (NaAlSi3O8) formation which has similarity to geopolymer compound. Fourier Transform Infra Red spectra show siloxo and sialate bond. These are typical functional groups that are found in geopolymer materials.Keyword: geopolymer, fly ash, aluminosilicate, alkali activator, albite, siloxo, sialateAbstrak: Pembangkit Listrik Tenaga Uap (PLTU) Suralaya menghasilkan fly ash (abu terbang) sekitar 219.000 ton per tahun. Fly ash memiliki silika dan alumina sebagai komponen utama yang dapat digunakan sebagai prekursor untuk geopolimer, suatu material polimer aluminosilikat tiga dimensi. Penelitian ini bertujuan untuk memanfaatkan fly ash untuk geopolimer yang dibuat dengan mencampur fly ash, agregat halus, dan aktivator alkali dalam cetakan kubik dan pengawetan dilakukan pada suhu kamar selama 7 dan 28 hari. Setelah 28 hari curing kekuatan tekan geopolimer mencapai 41,70 MPa. Karakterisasi XRD menunjukkan pembentukan Albite (NaAlSi3O8) yang memiliki kemiripan dengan senyawa geopolimer. Hasil spektroskopi Fourier Transform Infra Red (FTIR) menunjukkan ikatan siloxo dan sialate yang merupakan gugus fungsional khas yang ditemukan dalam geopolimer.Kata Kunci: geopolimer, abu terbang, aluminosilikat, alkali aktivator, albite, siloxo, sialate